An analysis of idiomatic expressions used in “The Call of the Wild” movie - Erika Vonny Cornelia; A. B. Prabowo Kusumo Adi; Maria Yosephin Widarti Lestari (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
Analysis of Idiomatic Expressions in the Movie "The Call of the Wild." The purpose of this research is to identify the different idiomatic that were used in the movie “The Call of the Wild” and to decipher their true meanings. Researchers employed the theory of McCarty and O'Dell and an idiom dictionary to address the set research topics. This study employs qualitative descriptive research techniques. Data analysis was done by reducing and displaying information to conclude. The study's conclusions are as follows: the six kinds of McCarty and O'Dell idiomatic idioms were discovered in the movie The Call of the Wild. The six categories of terms are similes idiom (7%), binomials idiom (5%), proverbs idiom (16%), euphemisms idiom (22%), cliches idiom (17%), and fixed statement idiom (33%). The most common form of idiomatic expression is a Fixed Statement idiom, the dominating idiom. On the other hand, binomial idioms are the style of idiomatic expression that The Call of the Wild uses the least. The implied meaning of idiomatic can be deduced from the context of the statement in the movie. Idioms cannot be understood in just one word or phrase, so they must be understood in one sentence or paragraph to understand the meaning of the original context.